How should virtual currencies be regulated in South Africa to prevent their use for money laundering - Lasker, Keegan (Department of Private Law, 2026)
Over the past ten years there have been a number of innovations which have disrupted the financial sector, caused by technological advances which have infiltrated and continue to infiltrate the banking and financial sector. These innovations which have brought together 1 Finance and Technology and is known as the Fin-tech revolution , bringing about changes in the areas of Finance, Investing, Real Estate, Crypto and Blockchain Lending, and Payments. The focus of this mini-thesis will however only be on Virtual Currencies (VC) and the risks they pose to the financial sector, which when summed up can be understood as being money laundering and terrorist financing risks, which clearly shows a need for adequate regulation. As a result of the Fin-tech revolution a number of new technological development have infiltrated the financial sector. One of the most innovative developments is VC, the term 'Virtual Currency', as defined by the Financial Action Task Force (FATF) refers to a digital representation of value that can be digitally traded and is able to function as a medium of exchange and/or a unit of account and/or a store value, but which does not have legal tender status.2 The manner and speed at which VC have infiltrated the financial sector solely stems from users ability to transact and to invest therein and to transact therewith. The South African Reserve Bank (SARB) has advised users to approach VC with extreme caution, but despite 3 this warning there has to date been no legislation to regulate VC.